2009
DOI: 10.2340/16501977-0366
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin A for treatment of upper limb spasticity following stroke: A multi-centre randomized placebo-controlled study of the effects on quality of life and other person-centred outcomes

Abstract: Although no change in quality of life was demonstrated using the AQoL, botulinum toxin type A was found to be safe and efficacious in reducing upper limb spasticity and improving the ability to achieve personal goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 24 publications
9
136
1
6
Order By: Relevance
“…Eight trials [44][45][46][47][48][49][50][51] and four systematic reviews [53][54][55][56] were published following the start of this study in 2005. Details of our literature search strategy, methodological appraisal of the papers, overview of the studies, and a summary of the systematic reviews can be found in Appendix 1.…”
Section: Review Of the Evidence For Treating Upper Limb Spasticity Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Eight trials [44][45][46][47][48][49][50][51] and four systematic reviews [53][54][55][56] were published following the start of this study in 2005. Details of our literature search strategy, methodological appraisal of the papers, overview of the studies, and a summary of the systematic reviews can be found in Appendix 1.…”
Section: Review Of the Evidence For Treating Upper Limb Spasticity Dumentioning
confidence: 99%
“…Sixteen randomised controlled trials (RCTs) [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and five systematic reviews [52][53][54][55][56] evaluating the clinical effectiveness of botulinum toxin as a treatment for upper limb spasticity after stroke have been published. Eight trials [44][45][46][47][48][49][50][51] and four systematic reviews [53][54][55][56] were published following the start of this study in 2005.…”
Section: Review Of the Evidence For Treating Upper Limb Spasticity Dumentioning
confidence: 99%
“…31 Botulinum toxin type A alone was shown to be effective for reducing spasticity in several double-blind, placebocontrolled, randomized controlled trials. [8][9][10][11][12] Botulinum toxin type A was shown to be an effective treatment of painful localized contractures in RHT, even without central nervous system lesions. 32 Therefore, BoNT-A may be a useful option for painful localized contractures that do not respond to standard treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4 Botulinum toxin type A has already been shown to be effective in reducing poststroke upper limb spasticity in some double-blind, placebocontrolled, randomized, controlled trials. [8][9][10][11][12] Moreover, BoNT-A has been used in conjunction with physiotherapeutics to improve function and decrease pain 13,14 and spasticity. 6,15,16 Neurodynamic mobilization (NM) is a form of manual therapy that directs force to neural structures through positioning and movement of multiple joints.…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly used as a person-centred outcome measure in research evaluations of outcome following spasticity intervention [16][17][18][19][20] , and is recommended as a method of recording patient-reported outcomes in guidelines for management of spasticity with Botulinum toxin 21 .…”
Section: Procedurementioning
confidence: 99%